Taxonomic study of the genus Assara Walker (Lepidoptera, Pyralidae, Phycitinae) in NE China, with description of a new species - Qi, Mu-Jie; Han, Hui-Lin; Park, Bo-Sun; Bae, Yang-Seop (Zootaxa, 2014)
Four species of the genus Assara Walker, 1863 are revised from NE China. Among them, Assara yanbianensis Bae & Qi sp. n. is described as new to science and A. terebrella (Zincken, 1818) is newly recorded from China. A key to the NE Chinese species of the genus Assara with illustrations of adults and genitalia are presented.